COLLODION BABY SYNDROME: A CASE REPORT FROM PIMS HOSPITAL, ISLAMABAD (Journal of Medical & Health Sciences Review, 2025)
Collodion Baby Syndrome (CBS) represents a distinctive and uncommon congenital disorder characterized by a striking clinical presentation  of  collodion  membrane  upon  birth. Collodion baby, also known as 'collodion fetus,' is frequently observed in various forms of congenital ichthyoses, many of which follow an autosomal recessive pattern of inheritance. These conditions include lamellar ichthyosis (LI), congenital ichthyosiform erythroderma (CIE), and self-healing collodion baby.¹ This case report describes the intricate dermatological challenges encountered in the management of a neonate diagnosed with CBS, emphasising the nuanced complexities that clinicians must confront in providing optimal care. A premature female infant was born at 35 weeks via emergency cesarean section who presented with a parchment-like membrane covering her entire body, which is a typical hallmark of CBS. She was taken to the Neonatal Intensive Care Unit where a multidisciplinary management approach encompassed meticulous skin care and assessment of transcutaneous water loss to optimize skin hydration. Vigilant monitoring of electrolyte imbalances as well as the potential complications of infection and fluid imbalance were essential components of the comprehensive care plan. Despite all efforts, the baby died on the fourth day of life due to a severely compromised epidermal barrier and its complications. In cases such as these, prompt identification and treatment is vital.